The Influence Of Cultural Values On The Implementation Of Education: A Comparison With Education Systems In Other Countries - Depi Fibriyanti; Ade Putra Tri Prima; Asbani Asbani; Kashardi Kashardi; Adi Asmara (Jurnal Pendidikan Rafflesia, 2026)
Cultural values ​​play a crucial role in shaping a country's education system, encompassing curriculum, learning methods, discipline, and educational objectives. This study aims to analyze the influence of cultural values ​​on the delivery of education through a comparison of the education systems of Finland, Japan, South Korea, and Singapore. The method used in this study is a literature review with a descriptive-comparative approach. Data were obtained from various scientific sources such as journals, books, and international education reports. The results show that each country has educational characteristics influenced by the cultural values ​​of its society. Finland emphasizes equality, freedom, and student well-being, creating a flexible education system with minimal academic pressure. Japan prioritizes discipline, responsibility, cooperation, and respect for others, reflected in school culture and character education. South Korea is influenced by a competitive culture and a strong work ethic, resulting in an education system oriented toward academic achievement. Meanwhile, Singapore integrates the values ​​of pragmatism, multiculturalism, and technological mastery into its education system to support the development of superior and adaptive human resources. This comparison demonstrates that the success of an education system is inseparable from the cultural values ​​that develop within society. Therefore, the development of education in Indonesia needs to consider relevant local cultural values ​​in order to be able to create an education system that is high quality, has character, and is in accordance with the needs of the times.